Newsette: Balitang Aklatan - July 2002 - De La Salle University Libraries (Animo Repository, 2002)
What's Inside: ASRC Holds Paper Show Computerized Reservations at Instructional Media Services Faculty and Co-Academic Personnel (CAPs) Activities Garcia Conducts Workshop on On-line Searching Valenzuela Lectures at DLSU-Dasmariñas At the ABAP BookFair Dialogue through Digital Libraries ... A Japan Experience by Jocelyn L. Ladlad - EDRC/ASRC Librarian Library Access to Central Clearance Database Velasquez Donation Want to Study in France? Visitors Donors Recent Acquisitions Instructional Media Resources Archives Resources Book Acquisitions (July 2002)